Unfair terms in Islamic banking contracts: realizing Maqasid al-Shariah towards banking consumer protection in Malaysia - Abu Bakar, Noor Mahinar; Mohd. Yasin, Norhashimah (2016)
The use of unfair contract terms in Islamic banking contracts remains a serious problem in Malaysia. Most Islamic banking contracts are in standard form contracts, also known as ‘adhesion contracts’ which are predrafted by the party with strong bargaining power in the contract and contain terms that are potentially unfair. These contracts are presented on a ‘take it or leave it’ basis and non-negotiable, leaving banking consumers no realistic opportunity to bargain for more favourable terms, subsequently resulting in an unfair transaction. Further, the unfair contract terms have greater implications on the realization of Maqasid al- Shariah, as it does not comply with the principles of protecting public interests (maslahah), honesty, trustworthy, financial transparency, prevent harm/hardship and al-‘adl wal-ihsan (justice with benevolence) in the circulation of wealth in banking transactions. This paper aims to analyze various legal documentations of Islamic banks in Malaysia in the light of Maqasid al-Shariah in order to propose a fair, transparent and consumer-friendly banking contracts. This paper suggests that the unfair contract terms in legal documentation of various Islamic banks and the inequality of bargaining power (ghubn) in banking industry, which resulted in the rights of banking consumers being infringed, have failed to realize the Maqasid al-Shariah. Thus, it justified the need to protect banking consumers from unfair contract terms as well as sending a strong message to the bankers to do fair trading and transparency in dealings, such that unfair terms will not be tolerated. This paper adopts a combination of theoretical and content analysis methodology.